ANALYSIS of the FLOW of BRINKMAN-TYPE NANOFLUID USING GENERALIZED FOURIER'S and FICK'S LAWS - Sheikh, N.A. (World Scientific, 2022)
The enhancement of the working ability of the industrial fluid is the need of the present era; nanofluid is an emerging field in science and technology. In this study, the Brinkman-type fluid model is used and is generalized using the Fourier's and Fick's laws. The graphene oxide nanoparticles are dispersed in the base fluid water. The fractional partial differential equations are then solved via the Laplace and Fourier transform method. The obtained solutions for velocity, heat transfer, and mass transfer are plotted in graphs. The results show that velocity profile decreases for Brinkman-type fluid parameter and volume fraction of the nanoparticles. The plot for the fractional parameter shows that different plots can be drawn for a fixed time and other physical parameters, which is the memory effect. Â© 2022 World Scientific Publishing Co. Pte Ltd. All rights reserved.